2005
DOI: 10.1073/pnas.0503681102
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between interstitial flow and VEGF directs capillary morphogenesisin vitrothrough a gradient amplification mechanism

Abstract: Cell organization is largely orchestrated by extracellular gradients of morphogenetic proteins. VEGF, an essential factor for capillary formation, is stored in the extracellular matrix, but the mechanisms by which it and other matrix-bound morphogens are mobilized to form spatial gradients are poorly understood. Here, we suggest an efficient mechanism for morphogen gradient generation by subtle biophysical forces in an in vitro model of capillary morphogenesis. Using a fibrin-bound VEGF variant that is release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
243
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 256 publications
(257 citation statements)
references
References 34 publications
11
243
2
1
Order By: Relevance
“…In addition to regulating function, fluid flow is also an important regulator of lymphatic morphogenesis or lymphangiogenesis, and has been shown to drive lymphatic capillary organization in dermal wound healing models [45,46] as well as in vitro culture models [47][48][49]. Without flow, as in the case of lymphedema, lymphatic endothelium becomes hyperplastic (i.e.…”
Section: Lymphatic Physiology and Neogenesismentioning
confidence: 99%
“…In addition to regulating function, fluid flow is also an important regulator of lymphatic morphogenesis or lymphangiogenesis, and has been shown to drive lymphatic capillary organization in dermal wound healing models [45,46] as well as in vitro culture models [47][48][49]. Without flow, as in the case of lymphedema, lymphatic endothelium becomes hyperplastic (i.e.…”
Section: Lymphatic Physiology and Neogenesismentioning
confidence: 99%
“…where K 0 is the hydraulic conductivity of the gel, m is the viscosity of the medium ($0.75 cp for 20% serumcontaining endothelial cell medium at 378C (Helm et al, 2005)), and 5P is the imposed pressure gradient (¼ dP/dr). We can integrate over the radius and estimate K 0 from the slope of DP versus Q:…”
Section: Flow Characterizationmentioning
confidence: 99%
“…We compared static versus flow conditions on LECs, as flow was previously shown to promote lymphatic capillarogenesis (Boardman and Swartz, 2003;Ng et al, 2004), as well as the effects of matrix-bound VEGF on LEC and BEC morphogenesis under flow (Helm et al, 2005) for 10 days. We found that interstitial flow of 1-2 mm/s induced from a 5 mm pressure drop (Fig.…”
Section: Capillary Morphogenesis Under Flow and A 2 Pi 1-8 -Vegf 121mentioning
confidence: 99%
“…The interstitial fluid flow associated with edema, even though it can be extremely slow, can have important effects on tissue morphogenesis and function, cell migration and differentiation and matrix remodeling, among other processes [108]. Abnormally increased interstitial flow rates can occur during low-grade inflammation and can also trigger fibroblasts to differentiate or remodel the extracellular matrix, contributing thus to the development of tissue fibrosis [107,[109][110][111][112]. Interstitial flow may significantly alter the distribution of metalloproteinases and lymphatic growth factors, inducing lymphatic endothelial cell migration and capillary morphogenesis [107,110].…”
Section: Splanchnic Interstitium Mesenteric Lymphatics and Peritoneamentioning
confidence: 99%